Quantification of Vegetation Arrangement and Its Effects on Longitudinal Dispersion in a Channel. Issue 5 (25th May 2019) - Park, Hyoungchul; Hwang, Jin Hwan
Abstract: In nature, aquatic vegetation is one of the important factors—along with hydraulic characteristics and geometric configuration—determining the dispersion of scalars. Previous research has studied the effects of vegetation on longitudinal dispersion, varying plant population with uniform arrangement. However, since vegetation grows more often in clumped and heterogeneous rather than uniform patterns, the present work investigates the effects of the vegetation arrangement on the flows characteristics such as longitudinal dispersion, mean velocities, and drag coefficients. Several types of vegetation arrangement are described with the isometric and allometric concept and quantified with the standardized Morisita index. Laboratory experiments were performed to investigate variations of hydraulic parameters and longitudinal dispersion coefficients according to vegetation arrangements, which were quantified with the standardized Morisita index. The hydraulic parameters of mean velocity, turbulent kinetic energy, and drag depend on the vegetation arrangements, and in particular, the longitudinal dispersion coefficient varies with these arrangements by a factor of 4 or more. Key Points: The standardized Morisita index can compare vegetation arrangements quantitatively and varies with dispersion parameters The longitudinal dispersion gets larger as the patterns of vegetation become more allometric even with the same density Vegetation in 2‐D allometric arrangement generates velocity fluctuations in the lateral direction, increasing of longitudinal dispersion